. CONDITIONS AND DETERMINANTS OF THE ACADEMIC STAFF PROFESSIONAL DEVELOPMENT IN THE MODERN SCHOOL - S. L. Fomenko (Russian State Vocational Pedagogical University, 2015)
The paper reveals the research findings concerning a complicated process of academic staff formation in the secondary school. The main determinants of the process include the discrepancy between the actual development level of academic staff and the existing requirements of pedagogic society. The author denotes the main motives for academic staff development: moral and financial incentives for professional growth, new educational tasks, unsatisfactory social status of educational institution, etc; and identifies the complex of objective and subjective conditions positively affecting the given process. According to the author, the main priority should be given to the methodological provision of academic staff, integration of their activity, and stimulation of informational, methodical, and organizational channels of school activity. In conclusion, the paper considers the principles of life-long teacher training, corporate cooperation, partnership and solidarity, and discusses the technological structure of academic staff development, based on the competence model of education.